Belief pills and the possibility of moral epistemology - Sinclair, Neil (Oxford University Press, 2017)
I argue that evolutionary debunking arguments are dialectically ineffective against a range of plausible positions regarding moral truth. I first (§1) distinguish debunking arguments which target the truth of moral judgements from those which target their justification. I take the latter to rest on the premise that such judgements can be given evolutionary explanations which do not invoke their truth (§§2-3). The challenge for the debunker is to bridge the gap between this premise and the conclusion that moral judgements are unjustified. After briefly discussing older attempts to bridge this gap (§§4-5), I focus on Joyce’s recent attempt, which rests on the claim that ‘we do not have a believable account of how moral facts could explain the mechanisms and forces which give rise to moral judgements’ (§6). I argue that whether or not there is such an account depends on what it is permissible to assume about moral truth in this context. Further, I suggest that it is reasonable to make assumptions about moral truth which allow for the possibility of at least partial moral epistemologies (§6.2). The residual challenge for the debunker is to show that these assumptions are unreasonable in a way which doesn’t render their debunking argument superfluous.